APLIKASI TEBAK TEPAT PETA 34 PROVINSI DI INDONESIA DENGAN ADOBE AIR (Information Technology and Telematics, 2014)
Abstract -- Social science is one of the subjects that exist in education world, which in there, there is a topic about map. But, many children now that dislike about the studying model system because of something such as lazy and uninterested on the studying method. That things can be solved by any studying applications such as android based and mobile application based, which chidren are very like the interactive studying method that will be packed in a application or game, so it can be wished children can studying when they play. This application will be built by Adobe Flash Pro CS 6, Action Script 3.0 and Adobe AIR. The application that we make, can give any questions to children such as where the position of 34 Indonesia’a provinces are that will be asked with animation added if their answer is true or false, which this application is made with only 34 Indonesia’s province area, so children can easier to understand and know the provinces in Indonesia area. Keyword—Adobe AIR, Adobe Flash Pro CS6, Android, Action Script 3.0, Application Guess Correctly map of 34 Province in Indonesia